(untitled) (Tanzania Medical Journal, 2017)
Introduction: Chronic end-organ damage among the sicklers is frequently diagnosed in Tanzania, but rarely involves multiple organs in a single patient.Case report: A 26-year-old Tanzanian black-sickler woman presented with features related to avascular necrosis of the right hip, left ventricular hypertrophy, pulmonary hypertension, Chronic Kidney Disease and Cholelithiasis. Despite the management given, her condition is still deteriorating.Conclusion: Prevention of these complications through screening and early diagnosis with a concurrent timely treatment should be advocated by all health-care providers